Laporan Kasus Berbasis Bukti: PENGARUH KOMPRES DINGIN TERHADAP PENURUNAN NYERI LUKA PERINEUM - Rachmatina, Marha Putri; Sofiyanti, Santi; Yulinda (Jurnal Kesehatan Siliwangi, 2024)
Perineal wounds are often causes pain and discomfort in patients, thereby reducing mobilization and inhibiting the wound healing process. Cold compresses have a local analgesic effect, reducing nerve sensitivity and lowering the pain threshold and reducing swelling. The aim of this research is to apply cold compresses as a method to reduce stitching wound pain during postpartum care.  This research method involves searching for articles using e-data search engines based on Pubmed, Science Direct, and Google Scholar for 2013-2023 with the criteria of original articles with experimental methods. From the search results, 3 articles were obtained that met the criteria. Applying cold compresses during the postpartum period as a non-pharmacological intervention can be an alternative to reduce pain in perineal wounds.